Comparison of long‐term patency after endovascular therapy for superficial femoral artery occlusive disease between patients with and without hemodialysis. Issue 6 (23rd December 2015) - Matsumi, Junya; Tobita, Kazuki; Shishido, Koki; Mizuno, Shingo; Yamanaka, Futoshi; Murakami, Masato; Tanaka, Yutaka; Takahashi, Saeko; Akasaka, Takeshi; Saito, Shigeru
Abstract : Objective: To compare long‐term patency after endovascular therapy (EVT) for superficial femoral artery (SFA) occlusive disease between patients with hemodialysis (HD; HD+) and those without HD (HD−). Background: Long‐term patency after EVT for SFA occlusive disease in HD+ remains unknown. Methods: EVT to SFA was successfully performed in 382 consecutive patients during 2004–2011. Cox proportional hazard model estimated the hazard ratio (HR) for the loss of primary patency (PP), secondary patency (SP), and amputation‐free survival (AFS) in HD+. Binominal logistic regression analysis calculated the propensity score (PS) for covariates with a P value of <0.2 for HD as a dependent variable. HRs were adjusted for PS in multivariate analysis using the Cox proportional hazard model. Results: PP and SP in HD+ and HD− were 47.9 and 79.4% and 68.4 and 92.5%, respectively, 4 years after EVT. There were no procedure‐related amputations or in‐hospital deaths. Adjusted HRs for the loss of PP, SP, and AFS were as follows: loss of PP, adjusted HR 2.010, 95% CI 1.157–3.492, P  = 0.013; loss of SP, adjusted HR 2.927, 95% CI 1.236–6.933, P  = 0.015; and loss of AFS, adjusted HR 1.665, 95% CI 0.994–2.791, P  = 0.053. Conclusions: Although HD+ had more than double the risks for loss of PP and SP than HD−, EVT to SFA in HD+ was found to be safe with an acceptable PP and SP. © 2015 Wiley Periodicals, Inc.